Aging and infectious diseases: workshop on HIV infection and aging: what is known and future research directions. - Effros, Rita B; Fletcher, Courtney V; Gebo, Kelly; Halter, Jeffrey B; Hazzard, William R; Horne, Frances McFarland; Huebner, Robin E; Janoff, Edward N; Justice, Amy C; Kuritzkes, Daniel; Nayfield, Susan G; Plaeger, Susan F; et al. (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2008)
Highly active antiretroviral treatment has resulted in dramatically increased life expectancy among patients with HIV infection who are now aging while receiving treatment and are at risk of developing chronic diseases associated with advanced age. Similarities between aging and the courses of human immunodeficiency virus (HIV) infection and acquired immunodeficiency syndrome suggest that HIV infection compresses the aging process, perhaps accelerating comorbidities and frailty. In a workshop organized by the Association of Specialty Professors, the Infectious Diseases Society of America, the HIV Medical Association, the National Institute on Aging, and the National Institute on Allergy and Infectious Diseases, researchers in infectious diseases, geriatrics, immunology, and gerontology met to review what is known about HIV infection and aging, to identify research gaps, and to suggest high priority topics for future research. Answers to the questions posed are likely to help prioritize and balance strategies to slow the progression of HIV infection, to address comorbidities and drug toxicity, and to enhance understanding about both HIV infection and aging.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aging; Antiretroviral Therapy, Highly Active; Child; HIV Infections; HIV-1; Humans; Immunity; Kidney Diseases; Liver Diseases; Metabolic Diseases; Middle Aged; Research